Characterizing inflammatory markers in highly aggressive soft tissue sarcomas. Issue 39 (30th September 2022) - Hashimoto, Kazuhiko; Nishimura, Shunji; Shinyashiki, Yu; Ito, Tomohiko; Akagi, Masao
Abstract : The prognosis for soft tissue sarcomas (STSs) is poor, especially for highly aggressive STSs, and the details of prognostic factors are unknown. This study aimed to investigate the prognostic factors for STSs in hematologic inflammatory markers. We included 22 patients with STSs treated at our institution. The STSs were histologically classified as follows: undifferentiated pleomorphic sarcoma, 7 cases; myxofibrosarcoma, 6 cases; and malignant peripheral nerve sheath tumor, 2 cases. The average patient age was 72.06 years. The numbers of patients who underwent each procedure were as follows: wide resection, 7; wide resection and flap, 2; marginal resection, 2; wide resection and radiation, 1; additional wide resection with flap, 1; wide resection and skin graft, 1; and radiotherapy only, 1. The median follow-up period was 26 months (3–92 months). The outcomes were as follows: continuous disease free, 6 cases; no evidence of disease, 6 cases; alive with disease, 1 case; and died of disease, 2 cases. Pretreatment blood examinations for C-reactive protein (CRP) and albumin levels; neutrophil, lymphocyte, and white blood cell (WBC) counts; and neutrophil/lymphocyte (N/L) ratio were investigated and correlated with tumor size, tissue grade, and maximum standardized uptake value (SUVmax). CRP level and neutrophil and WBC counts were positively correlated with tissue grade and SUVmax. N/L ratio was positively correlated with tumor size and SUVmax. CRP level, WBC and neutrophil counts, and N/L ratio may be poor prognostic factors for highly aggressive STSs.